Možnosti využití metody activity based costing v podnicích - Hyršlová, Jaroslava; Buchta, Miroslav (Univerzita Pardubice, 1999)
Activity based accounting represents a method of managerial cost accounting that allocates all internal costs to cost centers and cost carriers on the basis of the activities which caused the costs. The activity based costs of each product are calculated by adding the joint fixed and the joint variable costs to the direct costs of production. The strenght of ABC is that it enhances the understanding of the business processes associated with each product. It reveals where value is added and where value is destroyed.
Keywords: podniky; Náklady; manažerské účetnictví